Exochorionic morphology in four genera of Coeini: Pycina, Historis, Smyrna, and Tigridia (Nymphalidae: Nymphalinae) - Nieves-Uribe, Sandra; Llorente-Bousquets, Jorge; Flores-Gallardo, Adrián (Zootaxa, 2024)
We describe and compare the exochorion of four species currently recognized as belonging to the nymphalid tribe Coeini: Pycina zamba zelis, Historis a. acheronta, Smyrna karwinskii, and Tigridia acesta latifascia, based on specimens collected in the field and rehydrated specimens from entomological collections. We use a staining technique and scanning electron microscopy to observe and describe the main exochorionic characters as ridges, prebasal modifications, and microstructure. We include plates with photographs, drawings, and diagrams to provide a clear visualization of these structures. We also compiled exochorionic data of other Coeini species for comparison. The eggs of Coeini share the presence of colonnade ridges with those of Nymphalini but differ from the latter in in modifications in the prebase and base, which are its distinguishing characteristics and distinct from those in Nymphalini. Exochorionic characters indicate that Coeini contains three subtribes—Pycinina, Coeina, and Coloburina—which exhibit a morphological continuum in the prebasal/basal diagnostic characters within the tribe.